2022
DOI: 10.1038/s41416-022-01874-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian carcinosarcoma is a distinct form of ovarian cancer with poorer survival compared to tubo-ovarian high-grade serous carcinoma

Abstract: Background Ovarian carcinosarcoma (OCS) is an uncommon, biphasic and highly aggressive ovarian cancer type, which has received relatively little research attention. Methods We curated the largest pathologically confirmed OCS cohort to date, performing detailed histopathological characterisation, analysis of features associated with survival and comparison against high-grade serous ovarian carcinoma (HGSOC). Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 42 publications
(46 reference statements)
0
36
0
Order By: Relevance
“…Using a species-specific approach to parse mouse and human reads in a pan-cancer collection of gene expression data from xenograft samples, we demonstrated that, in the majority of tumor types, a greater proportion of transcripts from EMT-related genes originated from mouse stromal cells than from human tumor cells. In cancers known to have mesenchymal lineage components, such as ovarian carcinosarcomas 40 , expression of EMT-related genes did not originate predominantly from mouse stromal regions. Analysis of individual cell transcriptomes from tumor samples by scRNA-seq demonstrated that these EMT-related genes were highly expressed by CAFs.…”
Section: Discussionmentioning
confidence: 96%
“…Using a species-specific approach to parse mouse and human reads in a pan-cancer collection of gene expression data from xenograft samples, we demonstrated that, in the majority of tumor types, a greater proportion of transcripts from EMT-related genes originated from mouse stromal cells than from human tumor cells. In cancers known to have mesenchymal lineage components, such as ovarian carcinosarcomas 40 , expression of EMT-related genes did not originate predominantly from mouse stromal regions. Analysis of individual cell transcriptomes from tumor samples by scRNA-seq demonstrated that these EMT-related genes were highly expressed by CAFs.…”
Section: Discussionmentioning
confidence: 96%
“…2B) [68,72]. Heterologous sarcomatous elements are present in around half of cases, most commonly chondrosarcoma (30% cases) or rhabdomyosarcoma (20% cases) [68,72]; it has been suggested that chondrosarcoma is more common in OCS with endometrioid type carcinomatous components (Fig. 2B) [68].…”
Section: Ovarian Carcinosarcomamentioning
confidence: 98%
“…OCS is a rare diagnosis, accounting for <5% of cases, and represents the most aggressive form of OC (median survival approximately 13-24 months) [68,69]. Most are diagnosed at advanced stage (10-15% stage I, 10% stage II, 60-70% stage III, 10-20% stage IV), though recurrence and mortality risk is high across all stages [68,70,71]. Median age at OCS diagnosis is 66-70 years.…”
Section: Ovarian Carcinosarcomamentioning
confidence: 99%
See 2 more Smart Citations